Dampak Brand Image, eWOM, dan Price Terhadap Purchase Intention Mobil Bekas di Soloraya: Brand Trust Sebagai Variabel Mediasi - Rokhim Adi Nurhuseini; Aflit Nuryulia Praswati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the influence of Brand Image, Electronic Word-of-Mouth (eWOM), and Price on Purchase Intention of used car consumers in the Soloraya area, with Brand Trust as a mediating variable. The analytical approach applied is Partial Least Squares-Structural Equation Modeling (PLS-SEM) using purposive sampling technique. A total of 180 respondents were sampled, determined based on the multiplication of the number of indicators by five. Respondents consisted of individuals who were active in using social media as a means to search for and purchase used cars. The results showed that eWOM and Price had a significant effect on Purchase Intention, while Brand Image did not have a significant direct effect. In addition, Brand Trust was proven to play a significant role in influencing Purchase Intention and was a mediator in the relationship between Brand Image and eWOM on Purchase Intention. However, the Price variable did not have a significant effect on Brand Trust and also did not show a mediating effect on Purchase Intention. These findings emphasize the importance of Brand Trust in the purchasing decision-making process and underline the strategic role of social media in marketing used car products.